2019
DOI: 10.3389/fmech.2019.00017
|View full text |Cite
|
Sign up to set email alerts
|

Modeling for Design Optimization of Piston Crown Geometry Through Structural Strength and Lubrication Performance Correlation Analysis

Abstract: Piston subsystem is subjected to very complex but dynamic forces. Such forces include combustion gas force, inertial dynamics forces, lubricating action/damping forces, contact friction forces to name a few. Further, piston ring mounted in piston in addition to these forces experiences out ward springing action inside engine mounting due to inherent elasticity. To evaluate the strength of reciprocating piston, the simultaneous effect of all these forces should be considered, while simulating through finite ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Figure 3a, b shows the all-possible forces acting on a piston block and dynamic ring, which include inertial forces caused due to primary/reciprocating motion, inertial force caused due to secondary motion, gas dynamics force, lubricant reaction, friction force, and ring elastic forces. The forces involved due to elastohydrodynamic action are estimated by solving Reynolds equation, energy equation, and rheological equation simultaneously as per Mishra [9] and Mishra et al [16,25,29]. It also addresses the asperity contact issue through Greenwood and Tripp model for boundary co-action [47].…”
Section: Loading Conditions In a Dynamic Piston Assembly And The Forc...mentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3a, b shows the all-possible forces acting on a piston block and dynamic ring, which include inertial forces caused due to primary/reciprocating motion, inertial force caused due to secondary motion, gas dynamics force, lubricant reaction, friction force, and ring elastic forces. The forces involved due to elastohydrodynamic action are estimated by solving Reynolds equation, energy equation, and rheological equation simultaneously as per Mishra [9] and Mishra et al [16,25,29]. It also addresses the asperity contact issue through Greenwood and Tripp model for boundary co-action [47].…”
Section: Loading Conditions In a Dynamic Piston Assembly And The Forc...mentioning
confidence: 99%
“…Among the losses, the mechanical frictional loss is significant and accounts for more than 15% of the total input energy. Further, the majority of this loss is due to piston subsystem loss, which happens out of errant dynamics, contacting, and connecting actions [9], hence the need for technological development to reduce losses.…”
Section: Introductionmentioning
confidence: 99%
“…Minimum Axial thickness of ring t2 = 𝐷 10𝑍 (4) where z = number of rings Top land thickness b1 = 1.2 tH (5) Thickness of other land b2 = 0.75 t2 (6) Maximum thickness of barrel t3 =0.03D + t1 +0.4+4.5 (7) Thickness of piston barrel at lower end, t4= 0.3 t3…”
Section: Radial Thickness Of Ringmentioning
confidence: 99%
“…Thus, a piston needs to be designed to have low stress and temperature when operating. Recent study has shown that the amount of stress and temperature are affected by the shape of piston crown [4]. Selection of suitable piston crown decreases the temperature and stress on piston so that the piston will last longer.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the steep profile of the top ring face reduces friction. (Mishra et al 2019) introduced an optimization model for piston crown geometry using structural strength and lubrication performance correlation analysis. It was determined that the effects of all studied forces should be taken into account during the finite element simulation method.…”
Section: Introductionmentioning
confidence: 99%